Assessment of fipronil toxicity to the freshwater midge Chironomus riparius: Molecular, biochemical, and organismal responses - Monteiro, Hugo R. (2019)
Fipronil is a phenylpyrazole insecticide that entered the market to replace organochlorides and organophosphates. Fipronil impairs the regular inhibition of nerve impulses that ultimately result in paralysis and death of insects. Because of its use as a pest control, and due to runoff events, fipronil has been detected in freshwater systems near agricultural areas, and therefore might represent a threat to non-target aquatic organisms. In this study, the toxicity of fipronil to the freshwater midge Chironomus riparius was investigated at biochemical, molecular, and whole organism (e.g. growth, emergence, and behavior) levels. At the individual level, chronic (28 days) exposure to fipronil resulted in reduced larval growth and emergence with a lowest observed effect concentration (LOEC) of 0.081 μg L−1. Adult weight, which is directly linked to the flying performance and fecundity of midges, was also affected (LOEC = 0.040 μg L−1). Additionally, behavioral changes such as irregular burrowing behavior of C. riparius larvae (EC50 = 0.084 μg L−1) and impairment of adult flying performance were observed. At a biochemical level, acute (48 h) exposure to fipronil increased cellular oxygen consumption (as indicated by the increase of electron transport system (ETS) activity) and decreased antioxidant and detoxification defenses (as suggested by the decrease in catalase (CAT) and glutathione S-transferase (GST) activities). Exposure to fipronil also caused alterations in the fatty acid profile of C. riparius, since high levels of stearidonic acid (SDA) were observed. A comparison between exposed and nonexposed larvae also revealed alterations in the expression of globins, cytoskeleton and motor proteins, and proteins involved in protein biosynthesis. These alterations may aid in the interpretation of potential mechanisms of action that lead to the effects observed at the organism level. Present results show that environmentally relevant concentrations of fipronil are toxic to chironomid populations which call for monitoring of phenylpyrazole insecticides and of their ecological effects in freshwaters. Present results also emphasize the importance of complementing ecotoxicological data with molecular approaches such as proteomics, for a better interpretation of the mode of action of insecticides in aquatic invertebrates.